Pusat dan Periphery: Memahami Ketimpangan Ekonomi Antar Wilayah di Indonesia dan Solusi Pembangunan Berkelanjutan - Uken Sutisna; Rayhan Anwarul Umam; Buci Morisson (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Economic inequality between regions in Indonesia is still a major challenge, especially between Java, which is the center of the economy, and other regions such as Papua, Maluku, and Kalimantan, which are experiencing delays in development. This inequality is caused by several factors, such as centralized development policies, lack of infrastructure in certain regions, and high dependence on natural resources. This study aims to identify the causes of such inequality and offer solutions that can reduce the gap between regions. The approach used in this research is qualitative analysis by examining data related to economic growth, poverty rates, and the distribution of development between regions. The results show that inequality is mostly influenced by imbalances in investment and government attention to regions outside Java. Proposed solutions include decentralizing development, improving infrastructure in underdeveloped regions, and encouraging economic diversification to create more equitable opportunities. This research is expected to provide useful insights for a more inclusive development policy, so that all regions of Indonesia can develop sustainably and more equitably.